Smile Mask Development of Cryptography Performance of MOLAZ Method (MOLAZ-SM) - Shuwandy, Moceheb Lazam (2012)
Concealment of information is the most important things of interest to scientists and users alike. The work of many researchers to find new ways and methods for building specialized systems to protect the information from hackers. The method of those techniques AES and an adopted by the U.S. Department of Defense and launched in the eighties to the world. Even so, it parallels the evolution of these methods to penetrate systems. Researchers were developed this method for the protection of this algorithm. In the end of 2010 the researcher Engineer Moceheb Lazam during his studies at the Masters in the Universiti Utara Malaysia, develop this algorithm in order to keep the encryption and decoding. It was called MOLAZ. It used two algorithms AES 128 and AES 256 bits, and switching between them using special key (K,). In addition, it uses two keys to encryption and decryption. However, this method needs to be develops and supports the protection of information. Therefore, in 2011 appeared MOLAZ-SM. It presents a study is the development of this system by adding the mask technique to prevent the use of the style of repeated attempts to enter the key. The system depends on the base "If you enter a true key, you obtain to the truth information, but if you enter the false key; you obtains to the false information."